2012
DOI: 10.1093/carcin/bgs187
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status at breast cancer diagnosis: correlation with tumor characteristics, disease outcome, and genetic determinants of vitamin D insufficiency

Abstract: We correlated serum 25-hydroxyvitamin D(3) (25OHD) levels with tumor characteristics and clinical disease outcome in breast cancer patients and assessed the impact of genetic determinants of vitamin D insufficiency. We collected serum from 1800 early breast cancer patients at diagnosis, measured 25OHD by radioimmunoassay (RIA), and determined genetic variants in vitamin D-related genes by Sequenom. Multivariable regression models were used to correlate 25OHD levels with tumor characteristics. Cox proportional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
78
1
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 45 publications
13
78
1
3
Order By: Relevance
“…15-20; Table 1). Elevated circulating 25-OHD concentrations were associated with statistically significantly better survival in two studies (15,19), borderline statistically significant better survival in two (16,18), and no associations in last two (17,20). In one of the studies, lower circulating 25-OHD concentrations were associated with reduced survival among women who did not have chemotherapy [HR ¼ 1.15; 95% (15,17,19).…”
Section: Breast Cancermentioning
confidence: 93%
See 1 more Smart Citation
“…15-20; Table 1). Elevated circulating 25-OHD concentrations were associated with statistically significantly better survival in two studies (15,19), borderline statistically significant better survival in two (16,18), and no associations in last two (17,20). In one of the studies, lower circulating 25-OHD concentrations were associated with reduced survival among women who did not have chemotherapy [HR ¼ 1.15; 95% (15,17,19).…”
Section: Breast Cancermentioning
confidence: 93%
“…Elevated circulating 25-OHD concentrations were associated with statistically significantly better survival in two studies (15,19), borderline statistically significant better survival in two (16,18), and no associations in last two (17,20). In one of the studies, lower circulating 25-OHD concentrations were associated with reduced survival among women who did not have chemotherapy [HR ¼ 1.15; 95% (15,17,19). Circulating 25-OHD was associated with breast cancer survival in two of the other three studies (15,19), but the effect was limited to postmenopausal (HR, 0.15; 95% CI, 0.03-0.63), and not premenopausal women (HR, 0.93; 95% CI, 0.43-2.02) in one study (19).…”
Section: Breast Cancermentioning
confidence: 99%
“…A 4-year, populationbased, double-blind, randomized placebo-controlled trial has shown that improving calcium and vitamin D nutritional status substantially reduces all-cancer risk in postmenopausal women (Lappe et al, 2007). In addition to preventional role of vitamin D in BC development, various studies and a large cohort study investigating the association between vitamin D and BC survival have shown that women with vitamin D deficiency had a worse outcome (Robsahm et al, 2004;Porojnicu et al, 2007;Goodwin et al, 2009;Hatse et al, 2012). Additionally, it has been reported that 25-OHD levels were significantly lower in patients with locally advanced or metastatic BC patients (Palmieri et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Another emerging hypothesis proposes a role for vitamin D. Indeed vitamin D deficiency is common in postmenopausal breast cancer patients and is associated with worse outcome (Hatse et al 2012). Consequently, recent studies have reported that daily vitamin D supplements may have a protective effect on pathogenesis (Khan et al 2010, Rastelli et al 2011.…”
Section: Musculoskeletal Symptomsmentioning
confidence: 99%